Evaluating the Collagen Network of Articular Cartilage Using Contrast-Enhanced X-Ray Microscopy - Zhu, Ying; Bates, David; Sukhnandan, Nastassja; Ponjevic, Dragana; Matyas, John R.; Boyd, Steven K. (CMBES Proceedings, 2016)
No Abstract